EVALUATION ROAD DAMAGE USING THE PAVEMENT CONDITION INDEX (PCI) METHOD - Mochammad Ilham; Hanie Teki Tjendani; Jaka Purnama (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Roads are one of the infrastructures that play a very important role in development in a region for economic growth and public welfare, especially in Indonesia. when the construction of road pavements according to their function was introduced. In order to maintain the quality of road services, one of these efforts is to evaluate the condition of damage to the road pavement, namely by reviewing measurements of the condition of the road surface. This condition also applies to the Tambakboyo Highway section, Lamongan Regency, East Java Province, where, like other roads, every year there is traffic growth due to the increasing population, causing the road pavement construction to be damaged. In this study, a study was conducted to calculate road damage using the pavement condition index (PCI) method and to calculate the estimated cost of repairs that need to be done. The results of the analysis of the estimated cost of road repairs based on the budget plan) show that the total cost of the work, including 11% Value Added Tax, reached IDR 5,440,000.00. The largest cost component is found in STA 0+600 – 0+800, which requires quite large repair costs, in accordance with the pavement conditions that require patching.